The Need for Smarter Definitions and Practical, Timely Empirical Research on Information Disorder. Issue 8 (14th September 2018) - Wardle, Claire
Abstract : This article is based on a keynote delivered at the Future of Journalism conference at Cardiff University in September 2017. The speech was inspired by personal experiences and frustrations as a practitioner-academic leading a project designed to develop and test solutions to the challenges posed by information disorder. Arguing for closer relationships between journalism academics, news organizations and technology companies, this article outlines terminology and frameworks for making sense of information disorder, so those conversations can be based on shared definitions.